PERLINDUNGAN HUKUM TERHADAP ANAK LUAR KAWIN PASCA PUTUSAN MK NOMOR 46/PUU-VII/2010 - Sembiring, Febri; Tjowandi, Daniel Christian; Vigo, Dicky (JURNAL MUTIARA HUKUM, 2020)
Parents are responsible to their children to gave the education, clothing and the utility until they grow up. The children that born from parents in registered marriage by the state are called valid children. Otherwise, If a marriage of the children is not recorded as a children outside the marriage, then the negative impact of the children outside the marriage are birth certificate can not be made because the parents does not have marriage certificates. Section 43 paragraph 1 Laws of Marriage explained that the children that born outside the marriage just have a civil relationship with their mother and their mother's family. Every children who was born entitled to live, growing up, and thriving and get legal protection as a shape of justice and has been released the Supreme Court verdict of the Republic of Indonesia number 46 / PUU-VII / 2010 about Children Outside The Marriage can show the results of the DNA test as evidence of the biological relationship between the children and their father. This research method using an understanding of juridical sosiologis that the research based on the terms and applicable law with the phenomenon happened in the neighborhood in accordance with the practice. The resources used data is a literature review and the decision. Based on the understanding above, the author wants to write it in the form of Skripsi titled "Legal Protection To Children Outside The Marriage After The Decision of the Supreme Court Number 46 / PUU-VII / 2010". The formulation of the problems are what is the arrangement of children outside the marriage rights? What the consequences of the child outside the marriage according to the UUP? and How to protect children outside marriage rights after Supreme Court verdict Number 46 / PUU-VII / 2010.